2022
DOI: 10.3390/ani12223141
|View full text |Cite
|
Sign up to set email alerts
|

Use of Microorganisms as Nutritional and Functional Feedstuffs for Nursery Pigs and Broilers

Abstract: The objectives of this review paper are to introduce the structures and composition of various microorganisms, to show some applications of single cells as alternative protein supplements or energy feeds in swine and poultry diets, and to discuss the functional effects of microorganisms as feed additives on the growth performance and intestinal health of nursery pigs and broilers. Microorganisms, including bacteria, yeasts, and microalgae, have been commonly supplemented in animal diets because they are cost-e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 215 publications
(228 reference statements)
0
2
0
Order By: Relevance
“…Yeast cell wall components have also been used in nursery diets for their prebiotic effects, antibacterial properties, and toxin binding property [ 18 20 , 51 ]. A thorough review of bioactive compounds in microbial cell wall [ 52 ] characterized the composition of typical yeast cell wall including mannoprotein (35% to 40%), 1,3-β-glucan (50% to 55%), 1,6-β-glucan (5% to 10%), chitin (up to 3%) with immunomodulatory properties, antibacterial properties potentially beneficial to maintain healthy intestine and to reduce the occurrence of diarrhea as observed in this study. Yeast cell contents, however, are shown to be a good source of protein and also rich in nucleotides improving intestinal health when fed to nursery pigs reducing pathogenic invasion [ 21 , 53 , 54 ].…”
Section: Discussionmentioning
confidence: 91%
“…Yeast cell wall components have also been used in nursery diets for their prebiotic effects, antibacterial properties, and toxin binding property [ 18 20 , 51 ]. A thorough review of bioactive compounds in microbial cell wall [ 52 ] characterized the composition of typical yeast cell wall including mannoprotein (35% to 40%), 1,3-β-glucan (50% to 55%), 1,6-β-glucan (5% to 10%), chitin (up to 3%) with immunomodulatory properties, antibacterial properties potentially beneficial to maintain healthy intestine and to reduce the occurrence of diarrhea as observed in this study. Yeast cell contents, however, are shown to be a good source of protein and also rich in nucleotides improving intestinal health when fed to nursery pigs reducing pathogenic invasion [ 21 , 53 , 54 ].…”
Section: Discussionmentioning
confidence: 91%
“…Gram-positive bacteria are the main target for bacitracin due to the thicker peptidoglycan layer [35,36]. However, Gram-negative bacteria also contain peptidoglycan on the cell wall [37]. Xu et al [7] demonstrated that bacitracin can mitigate the effects of PWD caused by F18 + E. coli in nursery pigs.…”
Section: Discussionmentioning
confidence: 99%
“…Active dry yeast is the most common form of yeast supply in feed, but it can also be provided inactivated or fractionated, though at increased production costs. When administered live, yeast can act as a probiotic, improving gut health and growth performance [ 23 ]. Moreover, yeast biomass is a good source of macroelements such as calcium, phosphorus, and zinc, micronutrients such as selenium, and chromium or B-complex vitamins [ 24 ].…”
Section: Introductionmentioning
confidence: 99%